Serum blood urea nitrogen (BUN) sebagai penanda independen kematian di rumah sakit pada penderita infark miokard akut ST elevasi tanpa reperfusi dini - Hilfan Ade Putra Lubis; Tawanita Brahmana (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Introduction : Renal dysfunction has been associated to adverse cardiovascular outcomes, including in the setting of ACS, and has been routinely assessed with estimated creatinine clearance, serum creatinine or an estimated glomerular filtration rate (eGFR). However, these assays do not adequately assess acute changes in renal dysfunction. BUN level and BUN/creatinine ratio, may provide supplemental information regarding to renal function.Determine whether abnormal admission serum BUN and BUN/creatinine ratio in subjects presenting acute STEMI associated to other risk factors and whether they could be a predictor of inhospital deathMethods : It was a prospective cohort study of patients presenting acute STEMI without early reperfusion therapy (n = 43) included. Elevated BUN (> or • 25 mg/dl) and elevated BUN/creatinine ratio (> or • 5) were assessed on admission. Results : The incidence rate of elevated BUN and BUN/creatinin ratio were 18.6% and 9.3%. There was no significant relationship between elevated BUN and related risk factors (sex P = 0.57, hypertension P = 0.49, diabetes P = 0.61 and hypercholesterolemia P = 0.05). This study also showed no significant relationship between elevated ratio BUN/creatinine and related risk factors (sex P = 0.66, hypertension P = 0.6, diabetes P = 0.11, hypercholesterolemia P = 0.25). No significant increases of inhospital death found in patients with either elevated BUN (P = 0.10) or elevated BUN/creatinine ratio (P = 0.47).Conclusion : Elevated BUN and BUN/creatinine ratio on admission are not an independent predictors of inhospital death in this study.Key word : BUN; creatinine; STEM!; hospital death